2010
DOI: 10.1002/bit.22753
|View full text |Cite
|
Sign up to set email alerts
|

Production of cell culture (MDCK) derived live attenuated influenza vaccine (LAIV) in a fully disposable platform process

Abstract: The majority of influenza vaccines are manufactured using embryonated hens' eggs. The potential occurrence of a pandemic outbreak of avian influenza might reduce or even eliminate the supply of eggs, leaving the human population at risk. Also, the egg-based production technology is intrinsically cumbersome and not easily scalable to provide a rapid worldwide supply of vaccine. In this communication, the production of a cell culture (Madin-Darby canine kidney (MDCK)) derived live attenuated influenza vaccine (L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 71 publications
0
19
0
Order By: Relevance
“…While this technology is extremely robust, the use of established cell lines rather than fertilized hens' eggs for vaccine manufacture could have significant advantages, for example, better consistency of production, easier scaling-up, independence from egg supply and maintenance of chicken flocks, a reduced risk of microbial contamination, a non-animal origin process, a more homogeneous virus yield and the possibility of amplifying viruses that grow poorly in eggs [67,68]. The ability of cold-adapted LAIV strains to grow in MDCK cells has been evaluated in several studies, using small-scale and large-scale production processes, for both licensed LAIV backbones [69][70][71][72][73][74][75]. MedImmune established its own MDCK cell line, which allowed the growth of LAIV viruses to high titers with no significant impact on antigenic and growth properties [71,73].…”
Section: Cell Culture-based Laivsmentioning
confidence: 99%
“…While this technology is extremely robust, the use of established cell lines rather than fertilized hens' eggs for vaccine manufacture could have significant advantages, for example, better consistency of production, easier scaling-up, independence from egg supply and maintenance of chicken flocks, a reduced risk of microbial contamination, a non-animal origin process, a more homogeneous virus yield and the possibility of amplifying viruses that grow poorly in eggs [67,68]. The ability of cold-adapted LAIV strains to grow in MDCK cells has been evaluated in several studies, using small-scale and large-scale production processes, for both licensed LAIV backbones [69][70][71][72][73][74][75]. MedImmune established its own MDCK cell line, which allowed the growth of LAIV viruses to high titers with no significant impact on antigenic and growth properties [71,73].…”
Section: Cell Culture-based Laivsmentioning
confidence: 99%
“…African green monkey kidney-derived Vero cells, Madin-Darby Canine Kidney cells or PBS-1 cells) (Josefsberg and Buckland 2012;Whitford and Fairbank 2011). Both stirred (Chaubard et al 2010;George et al 2010) and wave-mixed (Genzel et al 2010;Magnusson et al 2011) SU systems operated with microcarriers as well as fixed bed bioreactors with fiber carriers (Moncaubeig 2013) have proven themselves.…”
Section: Established and New Applications For Dynamic Su Bioreactorsmentioning
confidence: 98%
“…Different studies, where MDCK and Vero cells were grown on microcarriers, revealed that tenfold higher cell densities and virus titers can easily be achieved when using wave-mixed and stirred bioreactors for virus production (e.g. Influenza, Polio, mink enteritis virus) (Genzel et al 2004(Genzel et al , 2006Hundt et al 2007;George et al 2010;Schouwenberg et al 2010;Thomassen et al 2012).…”
Section: Viral Vaccine and Virus-like Particle Productionmentioning
confidence: 99%
“…The cells can be easily adapted to and be grown in serum-free media, and in suspension, as well as on various microcarriers maintained under various bioreactor conditions. 93,[101][102][103][104][105][106][107][108] Subclones of MDCK cells adopted to grow in suspension and support robust virus production have also been described, 91,108,109 although adherent MDCK cells appear to support more robust virus production than suspension MDCK cells. 110 Influenza vaccines derived from MDCK cells are also safe and immunogenic.…”
Section: Mdck Cell-derived Influenza Vaccines: the Final Joust?mentioning
confidence: 99%